Azithromycin mitigates human rhinovirus impact on barrier integrity and function in non-diseased airway epithelium - Looi, Kevin; Sutanto, Erika N.; Iosifidis, Thomas; Berry, Luke J.; Kicic, Anthony; Stick, Stephen M. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionAzithromycin improves symptomology in various chronic airway diseases exacerbated by viral infections. However, the mechanisms underlying the apparent antiviral effects of azithromycin remain unclear.MethodsAirway epithelial cells from healthy children were cultured, expanded and differentiated into air-liquid interface cultures. Submerged and differentiated primary cultures were treated with 10 µM of AZM for 24 h and subsequently infected with human rhinovirus (HRV)-1b for 24 h. Virus receptor expression, replication, progeny release and inflammatory cytokines (IL-1β, −6, −8 and IP-10) were then measured. Barrier integrity was determined via qPCR, in-cell western (ICW), immunofluorescence confocal microscopy, confocal microscopy, transepithelial electrical resistance (RT) measurement and an apparent permeability (Papp) assay.ResultsTreatment with AZM for 24 h at the concentrations of 0.1, 1 and 10 µM did not have any significant impact on either cellular viability or cytotoxicity in un-infected cells. No significant effect on viral receptor, cytokine expression was observed in non-infected cells treated with 10 µM AZM. Similarly, there was no significant change in both occludin and ZO-1 expression in non-infected cells. However, claudin-1 gene expression was significantly reduced but corresponding protein expression was significantly increased following 10 µM AZM. Although RT was significantly lower, this was not corroborated by any significant change in epithelial permeability after 10 µM AZM treatment. Subsequent to HRV-1b infection, 10 µM AZM treatment significantly reduced cytotoxicity induced by infection. Viral receptor expression were not affected with AZM pre-treatment but a significant decrease in viral replication was observed. Except for IP-10, expression of IL-1β, −6, and −8 was significantly reduced. Gene and protein expression of key epithelial junctions were significantly higher in treated, infected cells, which were concomitant with epithelial barrier function.DiscussionsThis study identified that AZM can protect against HRV-1b-induced epithelial damage. Our data, demonstrating the antiviral, anti-inflammatory, and barrier-protective effects in vitro are strongly indicative of pleiotropic mechanisms of AZM for mitigating viral infection and its consequences. These effects are likely to contribute to the benefits observed in clinical trials of AZM in a number of chronic respiratory diseases.